Mass-loading, pile-up, and mirror-mode waves at comet 67P/Churyumov-Gerasimenko - Volwerk,M; Richter,I; Tsurutani,B; Gotz,C; Altwegg,K; Broiles,T; Burch,J; Carr,CM; Cupido,E; Delva,M; Dosa,M; Edberg,NJT; et al. (Annales Geophysicae, 2016)
. The data from all Rosetta Plasma Consortium instruments and from the ROSINA COPSinstrument are used to study the interaction of the solar wind with the outgassing cometary nucleusof 67P/Churyumov-Gerasimenko. During 6 and 7 June 2015, the interaction was first dominatedby an increase in the solar wind dynamic pressure, caused by a higher solar wind ion density. Thispressure compressed the draped magnetic field around the comet, and the increase in solar windelectrons enhanced the ionization of the outflow gas through collisional ionization. The new ionsare picked up by the solar wind magnetic field, and create a ring/ring-beam distribution, which, in ahigh-β plasma, is unstable for mirror mode wave generation. Two different kinds of mirror modesare observed: one of small size generated by locally ionized water and one of large size generatedby ionization and pick-up farther away from the comet.